Reaching the price conscious consumer: The impact of personality, generational cohort and social media use. Issue 4 (2nd December 2020) - Eastman, Jacqueline K.; Iyer, Rajesh; Eastman, Kevin L.; Gordon‐Wilson, Sianne; Modi, Pratik
Abstract: This research examines the impact of the Big Five personality traits and social media usage on price consciousness and determines if this impact is influenced by generational cohort by comparing 215 millennials with 300 baby boomers. The survey research with a national panel of U.S. consumers utilizes established scales along with asking about hours per week spent on social media. While the study found no generational differences in price consciousness, it did find differences in the Big Five personality traits as millennials are more open, but baby boomers are more conscientious, agreeable, and neurotic. The results suggest for millennials, extroverts are more price conscious and open individuals are less price conscious. The amount of social media usage does impact the level of price consciousness with those spending more time on social media being more price conscious. When comparing social media usage by cohort, there is no significant difference in terms of time spent on Facebook, but there are significant differences in time spent on Twitter, Instagram and Snapchat as millennials use all three of these sites more. Marketers can utilize social media to reach price conscious consumers and encourage extroverts to share/repost their business' price deals so their reference groups are aware of them. If businesses are trying to reach a broad target market including millennials and baby boomers, Facebook would be the best option, given its popularity across the cohort groups. If marketers are focusing on millennials, they may also want to have a presence on Instagram and Snapchat.